Analyzing Key Challenges for Implementing Circular Supply Chains in The Indian Electronics Sector: A Study Using AHP-Entropy Methodology - Surange, Vinod; Suthar, Janak (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
The Circular Economy (CE) prioritizes sustainable practices over conventional ones that deplete resources and generate waste, which is crucial for the electronics industry due to valuable metals and harmful compounds in E-waste. This study aims to identify core obstacles to establishing Circular Supply Chains (CSC) in India's electronic sector. This article delineates twenty-seven challenges encountered by the Indian electronic manufacturing Supply Chain (SC) through a comprehensive literature review and insights from industry experts from prominent electronic multinational companies. These challenges were subsequently categorized into five distinct groups. To examine the prioritization of critical obstacles, we used the Analytical Hierarchy Process (AHP) technique in conjunction with Shannon's Entropy approach. The model robustness was investigated by performing sensitivity analysis. The investigation uncovers the cost of sustainable materials, restricted financial capacity for implementing CSCM initiatives, absence of fiscal incentives for advancing CSC, focus on immediate economic gains, and lack of matured technology resources as core obstacles. These study outcomes will help decision-makers understand the main challenges in migrating to a CSC, and accordingly, they may pick out a successful navigation path. The scientific procedure of modeling obstacles' criticality prioritization will assist them in enhanced decision-making and focused efforts for incorporating circularity in SC.